Research technique of moisture condition in capillary-porous colloid bodies by the method of epr-spin labels - Погожих, Микола Іванович; Ромоданов, Ігор Сергійович; Пак, Андрій Олегович (Eastern-European Journal of Enterprise Technologies, 2012)
The method of investigation of boundary surface between form of bond of moisture in capillary-porous colloid body was described